Abandoning the Isochore Theory Can Help Explain Genome Compositional Organization in Fish - Vohnoutová, Marta; Sedláková, Anastázie; Symonová, Radka (International journal of molecular sciences, 2023)
The organization of the genome nucleotide (AT/GC) composition in vertebrates remains poorly understood despite the numerous genome assemblies available. Particularly, the origin of the AT/GC heterogeneity in amniotes, in comparison to the homogeneity in anamniotes, is controversial. Recently, several exceptions to this dichotomy were confirmed in an ancient fish lineage with mammalian AT/GC heterogeneity. Hence, our current knowledge necessitates a reevaluation considering this fact and utilizing newly available data and tools. We analyzed fish genomes in silico with as low user input as possible to compare previous approaches to assessing genome composition. Our results revealed a disparity between previously used plots of GC% and histograms representing the authentic distribution of GC% values in genomes. Previous plots heavily reduced the range of GC% values in fish to comply with the alleged AT/GC homogeneity and AT-richness of their genomes. We illustrate how the selected sequence size influences the clustering of GC% values. Previous approaches that disregarded chromosome and genome sizes, which are about three times smaller in fish than in mammals, distorted their results and contributed to the persisting confusion about fish genome composition. Chromosome size and their transposons may drive the AT/GC heterogeneity apparent on mammalian chromosomes, whereas far less in fishes.
Keywords: AT/GC genome composition; Fishes; Genome Size; Chromosomes, Mammalian; savčí chromozomy; isochory; zvířata; Mammals; ryby; GC-content evolution transposons; natural breaks; savci; délka genomu; Isochores; Cluster Analysis; shluková analýza; Animals